Peri-operative blood pressure changes in normotensive and hypertensive patients - Poh, K. S.; Lim, Thiam Aun; Ibrahim, Noor Airini (Malaysian Medical Association, 2007)
Controversy surrounds the acceptance of hypertension as an independent risk factor for anaesthesia. In an attempt to identify variables that are associated with increased haemodynamic instability during surgery, the blood pressure profiles of 128 patients were analysed. The two variables that contributed most to the instability were pre-operative control of blood pressure and anaesthetic technique. To reduce the fluctuation in blood pressure, it is advisable for patients to be given a regional anaesthetic. Current therapy for hypertension appears to exaggerate the depressant effects of anaesthetic drugs. Care must be taken not only to prevent hypertensive episodes during surgery, but also hypotension